ЭВОЛЮЦИЯ СКЛОНОВ ДОЛИН НИЗШИХ ПОРЯДКОВ НА ОСНОВЕ ПРЕДСТАВЛЕНИЙ О ГЕОМОРФОЛОГИЧЕСКОЙ ФАЦИИ (НА ПРИМЕРЕ НИЗКОГОРЬЯ ЮЖНОГО СИХОТЭ-АЛИНЯ) - Невский В.Н. (My University, 2006)
Geomorphologic facie of slopes is specified by two independent parameters: the steepness of the slope and mechanical composition of deposit (or characteristic of denuded slope surface). Using this idea author represents the scheme of mountain relief flattening under the condition of rhythmic fluvial activity. According to idealized scheme the slope evolution is directional discontinuous process, of which every episode includes denudation and accumulative stages. In the reality they may be not strictly separated.
Keywords: 551.4.037(235.47)